PERAWATAN KATETER URINE INDWELLING DENGAN CHLORHEXIDINE GLUCONATE 2% DALAM MENCEGAH INFEKSI SALURAN KEMIH DI RUANG RAWAT INAP RSUD TAMAN HUSADA BONTANG - Noviani Nastiti Susantiningdyah; Ninuk Dian Kurniawati; Sriyono Sriyono (Universitas Airlangga, 2019)
Introduction: Urinary tract infections that occur in hospitals are mostly caused by the installation of indwelling urinary catheter. Indwelling urinary catheter care is one way to prevent the occurrence of catheter-associated urinary tract infections. This study aimed to determine the effect of indwelling urinary catheter care by using clorhexidine gluconate 2% on the incidence of urinary tract infections at inpatient rooms of RSUD Taman Husada Bontang.Methods: The research employed a quasyexperiment posttest only design. Technique of sampling used non-probability sampling: consequtive sampling. The independent variabel was indwelling urinary catheter care. The dependent variabel was urinary tract infections. Data were collected by using colony count and types of bacteria on the fourth day. Data were analyzed by using Mann Whitney test with level of significance α<0,05.Results: The results showed that there was no difference in urinary tract infections between patients in treatment group who received indwelling urinary catheter care by using chlorhexidine gluconate 2% and patients in control group who received standard catheter care (p=0.138).Conclusion: Agent of perineal care does not influence the incidence of catheter associated urinary tract infections. Further studies should involve larger respondents and consider the characteristics of respondents such as using antibiotic, diabetes mellitus and urine production to obtain more accurate results.